Energy Accumulation and Dissipation of Coal with Preopening under Uniaxial Loading - Xin Wei; Hao Hu; Yang Li (Shock and Vibration)
Energy accumulation and dissipation play an important role during the entire process of rock failure. Some flaws, such as preexisting holes, will influence energy accumulation and dissipation. In order to investigate the energy evolution of coal specimen with preexisting holes under uniaxial compression through numerical approaches, the particle simulation method was used in numerical simulations. In this paper, the energy evolution of coal specimen was theoretically analyzed, and the influence of different hole arrangement, such as diameter, spacing, angle, and number, on the evolution characteristics of energy was also discussed. At the same time, the arrangement of the artificial boreholes for preventing the rockburst was explored. The results show that, compared with the intact coal specimen, the change of diameter, spacing, angle, and the number of holes weakened the coal specimen’s capacity to store energy and release strain energy. When the diameter, the vertical distance, and relative angle of preexisting holes were 15 mm, 10∼15 mm, and 60°, respectively, the energy storage limit reached optimal value. For arrangement of the artificial boreholes, the diameter, spacing, and angle can be designed on the basis of those optimal values. This study has a guiding significance in designing the arrangement of the artificial boreholes for mitigation of rockburst.